PELATIHAN PENULISAN DAN PUBLIKASI KARYA TULIS ILMIAH BAGI CALON IMAM KEUSKUPAN AGUNG MAKASSAR - Patrio Tandiangga; Anthonius Michael; Arwin Dama; Inelta Paseno; Yustina Ponglele (Jurnal Abdimas Bina Bangsa, 2024)
Not all of the prospective priests of the Makassar Archdiocese, especially those at the Anging Mammiri Higher Seminary, have good writing skills. So it needs to be accompanied intensively through the PkM which we will implement. The hope is that by providing this writing training, prospective priests will become more proficient and skilled and more motivated in producing writings based on their thoughts and reflections. The objectives of this training activity are; Firstly, prospective priests are able to express all thoughts, ideas and reflections into good written form and in accordance with applicable standards. Second, increasing the motivation and skills of prospective KAMS priests in terms of writing